Comparative Study of Indonesian Students' Mathematical Literacy Abilities with Other Countries in Terms of PISA Type HOTS - Deby Nurqamar; Iyan Rosita Dewi Nur (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Indonesian students often have difficulty in fulfilling mathematical literacy indicators which results in low mathematical literacy abilities of students in Indonesia. Not only that, the PISA study (which tests students' mathematical literacy skills in several countries) states that Indonesia occupies a lower position when compared to other countries. The purpose of this research is to find out several things that need to be improved to welcome the next PISA study. The method used is a literature study that aims to review past phenomena and phenomena that are currently happening. The results obtained in this study are that the mathematical literacy ability of Indonesian students is still low when compared to other countries such as China, Singapore, Japan, and Argentina. The conclusion obtained is that Indonesian students must start getting used to working on math exercise in HOTS (High Order Thinking Skills) type questions which can improve mathematical literacy skills